(untitled) (Fiep Bulletin - online, 2015)
Aiming to analyze and correlate with body composition, level of physical activity with the risk of coronary interstate bus drivers, the sample group consisted of 106 drivers (age 38.3 ± 8.5 years). The analytical plan and used the correlation BioEstat 5.0 by applying the Pearson equation. The results showed that drivers had a mean and standard deviation (SD) with a profile (BMI) for overweight (26.1 ± 3,9kg / m2), of these, 44.3% were overweight and 14.1% obese, and abdominal fat (WHR) in high-risk level (0.93 ± 0.07), although 29.2% were at high risk, very high risk 21.7% and 88.6% of motorists are at risk moderate to very high. Regarding the pattern of physical activity (IPAQ), 20.7% were sedentary, 38.6% are irregularly active B, 14.1% are irregularly active A, 25.4% active and less than 1% very active. The results also show no correlation to coronary risk factors between BMI and WHR variables, with values of r = 0.391 and p = <0.0001; since the BMI and Physical Activity Level subjects, variables shows a positive correlation to develop coronary risk factors, where r = 0.1696 and p = 0.0820; WHR and Physical Activity Level, likewise, viewed the positive correlation tendency to develop coronary risk factors with r = 0.1015 and p = 0.3003. In conclusion, we found that the bus drivers did not show normal levels in your body composition and that there is a predisposition to cardiac risk by the studied variables, except BMI and WHR which show no correlation to coronary risk factors among variables. Motorists investigated showed up suffering from overweight, abdominal obesity and cardiovascular risk as values above the normal range in anthropometric diagnosis.